Last instar larva of the critically endangered Oxyagrion franciscoi Machado & Bede, 2016 (Odonata: Coenagrionidae) from Serra da Canastra National Park - Fernandes-Pires, Camila Eduarda; Datto-Liberato, Felipe Henrique; Guillermo-Ferreira, Rhainer (Zootaxa, 2024)
Oxyagrion franciscoi Machado & Bede, 2016 is a critically endangered damselfly species endemic to the Serra da Canastra National Park, Brazil, a vital environmental reserve within the Cerrado hotspot for biodiversity conservation. Here we reared, illustrated, and described the last instar larva of O. franciscoi.